2006
DOI: 10.1007/s11010-006-9248-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gradual coronary artery occlusion and exercise training on gene expression in swine heart

Abstract: Gradual occlusion (O) of the swine left circumflex coronary artery (LCX) with an ameroid occluder results in complete O within 3 weeks, collateral vessel development, and compensatory hypertrophy. The purpose of this investigation was to determine the independent and combined effects of O and exercise training (E) on gene expression in the swine heart. Adult Yucatan miniature swine were assigned to one of the following groups (n = 6-9/group): sedentary control (S), exercise-trained (E), sedentary swine subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…We speculate that the responsiveness of the collateral-dependent region of exercisetrained pigs to dobutamine is perhaps due to unique regional adaptations of the ␤-adrenergic signaling pathway or other mechanisms, such as those associated with the faster Ca 2ϩ kinetics observed in the collateral-dependent region. Unique adaptations in the collateral-dependent myocardial region of exercise-trained pigs have been previously noted in this model (8). Although not measured in our study, previous reports (23,38) have suggested that differential expression of ␤-ARs, such as ␤ 2 -and/or ␤ 3 -ARs, altered phosphorylation status of ␤-ARs by ␤-AR kinase 1 or G protein-coupled kinase 2, and PKA may contribute to desensitization to ␤-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We speculate that the responsiveness of the collateral-dependent region of exercisetrained pigs to dobutamine is perhaps due to unique regional adaptations of the ␤-adrenergic signaling pathway or other mechanisms, such as those associated with the faster Ca 2ϩ kinetics observed in the collateral-dependent region. Unique adaptations in the collateral-dependent myocardial region of exercise-trained pigs have been previously noted in this model (8). Although not measured in our study, previous reports (23,38) have suggested that differential expression of ␤-ARs, such as ␤ 2 -and/or ␤ 3 -ARs, altered phosphorylation status of ␤-ARs by ␤-AR kinase 1 or G protein-coupled kinase 2, and PKA may contribute to desensitization to ␤-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 48%
“…Despite experimental and clinical evidence that exercise training enhances myocardial contractility in diseased hearts (16,18,19,30), the underlying cellular and molecular adaptations have only begun to be studied (8,21,39). Our data using the exercise traininginduced adaptations in a porcine model of chronic occlusion demonstrated that increased force development in the collateraldependent region after exercise training is associated with Ca 2ϩ sensitization of the myofilaments as well as faster intracellular Ca 2ϩ kinetics during stimulation.…”
Section: Discussionmentioning
confidence: 85%
“…15 Many studies have shown that ANF mRNA levels increase in response to a wide range of hypertrophic stimuli, including aging, long-term ␤-adrenergic stimulation, aortic constriction, thyroid hormone, hypertension, exercise training, and coronary artery occlusion. 27,28 Therefore, repeat induction of gene expression for ANF in the left ventricle is one of the most reliable markers of cardiac hypertrophy. Levels of ANF mRNA were significantly elevated in spontaneously hypertensive rats compared with normotensive Wistar-Kyoto rats and increased even further when hypertension-induced hypertrophy progressed to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…2. Relevance of the pig as a large animal model to study the innate immune system Pigs are of proven relevance for use in the study of human health priorities such as obesity (Brambilla and Cantafora, 2004), cardio-vascular disease (Boluyt et al, 2007), nutritional studies (Puiman and Stoll, 2008), and communicable diseases as pigs have anatomical (Swindle et al, 2012) and physiologic (Kuzmuk and Schook, 2011) characteristics comparable to humans. Due to their long-standing domestication (Barrios-Rodiles et al, 2005), there is a substantial amount of information regarding their husbandry making them a particularly attractive animal model.…”
Section: Introductionmentioning
confidence: 99%